2013
DOI: 10.1051/0004-6361/201220919
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse interstellar bands in fullerene planetary nebulae: the fullerenes – diffuse interstellar bands connection

Abstract: We present high-resolution (R ∼ 15 000) VLT/UVES optical spectra of two planetary nebulae (PNe; Tc 1 and M 1-20) where C 60 (and C 70 ) fullerenes have already been found. These spectra are of high quality (S/N > 300) for PN Tc 1, which permits us to search for the expected electronic transitions of neutral C 60 and diffuse interstellar bands (DIBs). Surprisingly, we report the non-detection of the most intense optical bands of C 60 in Tc 1, although this could be explained by the low C 60 column density estim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…By using the Spitzer formula (N ∼ 10 20 × (EQW/(λ 2 × f ))), where f is the oscillator strength of each C 60 transition (Sassara et al 2001), this translates into column densities of ∼2 × 10 13 , 4 × 10 13 , and 2 × 10 13 cm −2 . These column density limits are similar to those previously obtained in Tc 1 by García-Hernández & Díaz-Luis (2013). By following the latter work, we could in principle compare these column-density limits with estimates of the circumstellar density of C 60 molecules as derived from the IR C 60 emission bands.…”
Section: Electronic Transitions Of Neutral C 60 In Fullerene Pnesupporting
confidence: 85%
See 2 more Smart Citations
“…By using the Spitzer formula (N ∼ 10 20 × (EQW/(λ 2 × f ))), where f is the oscillator strength of each C 60 transition (Sassara et al 2001), this translates into column densities of ∼2 × 10 13 , 4 × 10 13 , and 2 × 10 13 cm −2 . These column density limits are similar to those previously obtained in Tc 1 by García-Hernández & Díaz-Luis (2013). By following the latter work, we could in principle compare these column-density limits with estimates of the circumstellar density of C 60 molecules as derived from the IR C 60 emission bands.…”
Section: Electronic Transitions Of Neutral C 60 In Fullerene Pnesupporting
confidence: 85%
“…García-Hernández & Díaz-Luis (2013) found no evidence of these strong neutral C 60 optical bands in absorption (or emission) in the fullerene PN Tc 1. The S/N in the M 1-20 optical spectrum is too low to search for neutral C 60 features in its spectrum (García-Hernández & Díaz-Luis 2013), but here we have searched the higher S/N (∼100 in the continuum around 4000 Å) spectrum of the PN IC 418 for the strongest electronic transitions of neutral C 60 mentioned above.…”
Section: Electronic Transitions Of Neutral C 60 In Fullerene Pnementioning
confidence: 90%
See 1 more Smart Citation
“…Thus, reaction of PAHs with fullerenes provides additional insight into fundamental astrochemistry between these two important classes of large cosmic molecules. For example, a better understanding of the carbon structures that produce the enigmatic diffuse interstellar bands (DIBs) can also be achieved by such investigations (38). Very recently, it has been shown that small PAHs, such as anthracene, can form a DielsAlder cycloaddition product in the gas phase (39).…”
Section: Gas-phase Reaction Of Fullerenes With Pahs Under Energeticmentioning
confidence: 99%
“…Furthermore, as circumstellar environments are typically significantly warmer and denser than diffuse ISM clouds, they provide additional, complementary regimes in which to characterize DIB behavior and thus their carriers. Searches for DIB features in circumstellar environments have been either unsuccessful or inconclusive in a variety of sources, from protostars to planetary nebulae (PNs; e.g., Le Bertre & Lequeux 1993;Oudmaijer et al 1997;García Hernández & Díaz-Luis 2013). Slightly more promising candidates have been found by Díaz-Luis et al (2015), who noted absorption features toward the PN Tc 1 at wavelengths consistent with DIBs blueshifted within the range of the nebular emission velocity; Dahlstrom et al (2013) and Oka et al (2013) interpreted some unusually broad and asymmetric DIBs toward the infrared (IR) source Herschel 36 as most likely due to excitation of the DIB carrier molecules by the local radiation field, but see also Bernstein et al (2015).…”
Section: Introductionmentioning
confidence: 99%